2020
DOI: 10.1038/s41401-020-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde protects against rat intestinal ischemia/reperfusion injuries by synergistic inhibition of NF-κB and p53

Abstract: Our preliminary study shows that cinnamaldehyde (CA) could protect against intestinal ischemia/reperfusion (I/R) injuries, in which p53 and NF-κB p65 play a synergistic role. In this study, we conducted in vivo and in vitro experiments to verify this proposal. SD rats were pretreated with CA (10 or 40 mg · kg −1 · d −1 , ig) for 3 days, then subjected to 1 h mesenteric ischemia followed by 2 h reperfusion. CA pretreatment dose-dependently ameliorated morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 104 publications
1
24
0
Order By: Relevance
“…DAPI staining is used to detect apoptosis in vitro [ 22 , 28 ]. The in situ observation in the IEC-6 battery configuration is shown in Figure 5(d) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DAPI staining is used to detect apoptosis in vitro [ 22 , 28 ]. The in situ observation in the IEC-6 battery configuration is shown in Figure 5(d) .…”
Section: Resultsmentioning
confidence: 99%
“…Histological evidence of intestinal I/R injury includes decreased villus height, increased cellular infiltrate, and mucosal sloughing [ 45 ]. And the increase of serum aminotransferase levels, such as AST and ALT, caused by remote organ injuries is also one of the characteristics of intestinal I/R injury [ 28 , 46 , 47 ]. Proinflammatory cytokines, such as TNF- α , IL-6, and IL-1 β , in serum of intestinal I/R animals are significantly increased [ 22 , 28 , 48 ], which is related to neutrophil activation and tissue damage caused by I/R [ 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that mesenteric I/R induced excessive intestinal (local) morphological changes, inflammation, oxidative stress, apoptosis, and upregulated p53 and NF- κ B pathway-related proteins in mesenteric I/R-injured rats and hypoxia/reoxygenation- (H/R-) injured intestinal epithelial cells-6 (IEC-6), and CA pretreatment significantly restored all the above-mentioned changes in mesenteric I/R-treated rats and H/R-treated IEC-6 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were randomly assigned to 5 groups (5 rats/group): (1) sham group: via the intragastric gavage (ig) route, rats were given a vehicle daily for 3 days before rat sham surgery; (2) sham+CA group: rats were subjected to sham surgery after pretreatment with CA (ig) with the concentration 40 mg/kg daily/3 days; (3) I/R group: via the intragastric gavage (ig) route, rats were given a vehicle daily for 3 days before they were induced with 1 h mesenteric ischemia and then reperfusion for additional 2 h; (4) I/R+CA (L) group: rats were subjected to I/R surgery after they were pretreated with CA (ig) with the concentration 10 mg/kg/day/3 days [ 18 , 34 ]; and (5) I/R+CA (H) group: rats were subjected to I/R surgery after they were pretreated with CA (ig) with the concentration 40 mg/kg/day/3 days [ 18 , 35 , 36 ]. The intragastric gavage suspension of CA in carboxymethyl cellulose (1% CMC) was prepared daily and freshly and given at 2 mL/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation